The sǎnce - Nixon, Joan Lowery (Orlando, Fla. : Harcourt, 2004)
A seance begun as a game when a young girl insists that she can communicate with the dead ends in murder when the lights suddenly go out and one of the participants suddenly vanishes.
790
Keywords: Seances -- Fiction; Texas, East -- Fiction; Mystery fiction